China–US trade: implications on conflicts. Issue 2 (4th May 2019) - Qiu, Larry D.; Wei, Xing
ABSTRACT: In this study, we examine various aspects of China's trade, the U.S.' trade, and the bilateral trade between the two countries. The analysis of each aspect has direct and indirect implications on trade conflicts between the two countries. We focus on important factors, such as the growth of trade, import penetration, increased competitiveness of Chinese firms, comparative advantages of Chinese goods, China's WTO entry and its compliance, and bilateral trade imbalance. While each of the factors can lead to trade frictions, individual factors will not have led to a large-scale trade war. These factors converge within a brief period and thus can be considered the China shock, thereby making other countries' adjustments to their economic structures difficult. Therefore, trade frictions are inevitable.